Recognition of host Clr-b by the inhibitory NKR-P1B receptor provides a basis for missing-self recognition. Issue 1 (December 2018) - Balaji, Gautham; Aguilar, Oscar; Tanaka, Miho; Shingu-Vazquez, Miguel; Fu, Zhihui; Gully, Benjamin; Lanier, Lewis; Carlyle, James; Rossjohn, Jamie; Berry, Richard
Abstract The interaction between natural killer (NK) cell inhibitory receptors and their cognate ligands constitutes a key mechanism by which healthy tissues are protected from NK cell-mediated lysis. However, self-ligand recognition remains poorly understood within the prototypical NKR-P1 receptor family. Here we report the structure of the inhibitory NKR-P1B receptor bound to its cognate host ligand, Clr-b. NKR-P1B and Clr-b interact via a head-to-head docking mode through an interface that includes a large array of polar interactions. NKR-P1B:Clr-b recognition is extremely sensitive to mutations at the heterodimeric interface, with most mutations severely impacting both Clr-b binding and NKR-P1B receptor function to implicate a low affinity interaction. Within the structure, two NKR-P1B:Clr-b complexes are cross-linked by a non-classic NKR-P1B homodimer, and the disruption of homodimer formation abrogates Clr-b recognition. These data provide an insight into a fundamental missing-self recognition system and suggest an avidity-based mechanism underpins NKR-P1B receptor function. Natural killer (NK) cells eliminate damaged cells, but spare healthy ones by recognizing their expressed ligands via NK inhibitory receptors. Here the authors solve the structure of an NK inhibitory receptor, NKR-P1B, bound to its ligand, Clr-b, with further data suggesting a weak interaction and informing on the basis of missing-self recognition.